Russia’s Accession to the WTO in the Mirror of Russian Print Media - Svetlana Barsukova; Anastasia Korobkova (Journal of Economic Sociology, 2014)
The debate about the risks and potential gains from WTO accession for Russia has been going on for a long time, both in the mass media and in the scientific community. Politicians, businessmen and experts community expressed their opinion on this issue active and emotionally. Each of these parties expected different effects from Russia’s entering to the WTO and used different arguments in the debate. The method of our study is content analysis of articles in the leading Russian periodical publications.In this paper we analyze the dynamics of the intensity of the debate on this issue and make an assumption about the possible causes of these fluctuations. We showed that the intensity of the debate on this issue depended on various factors such as the passage of diverse stages of the negotiations, the interests of supporters and opponents of joining the WTO, the presence of competing (more interesting for the mass media and the people) topics.We pay particular attention to the arguments of discussion and analyze the main points of proponents and opponents of entering the WTO. We consider the basis of their arguments: on the terms of Russia’s accession to this organization or on the fact of entering. Proceeding from this, it is concluded that there are weighty arguments or that they are abstract and theoretical. We also consider the differences in the arguments used by businessmen, politicians, experts and journalists.If we look at the dynamic aspect, it should be noted that in the period after the entry debate has become less emotional. There was also a decline in optimism about the prospects of membership in the organization. In part, this may be due to decreased activity of politicians as participants of discussions, which were the most active supporters of accession to the WTO.